2019
DOI: 10.3390/su11041211
|View full text |Cite
|
Sign up to set email alerts
|

Inclusions in and Exclusions from the S&P 500 Environmental and Socially Responsible Index: A Fuzzy-Set Qualitative Comparative Analysis

Abstract: Socially responsible investment (SRI) indices provide an interesting opportunity to analyse the links between corporate financial performance (CFP) and corporate sustainability performance (CSP). However, few studies focus on the antecedents of inclusions in and exclusions from SRI indices. Specifically, the implications of corporate sustainability disclosure (CSD) have been largely ignored in this field. Furthermore, previous literature on the CSP-CSD-CFP links shows inconclusive results that have been attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 105 publications
(270 reference statements)
0
14
0
1
Order By: Relevance
“…Most environmental performance research has been focused on determining the internal and external factors and identifying the related laws to verify the relationships between corporate environmental performance and financial performance [33][34][35][36]. For example, Yin and Ma found that the environmental standards adopted by enterprises could not be equated with their actual environmental performances [36], Dawkin and Fraas collected data from 500 S&P companies and proved that there was a U-type relationship between environmental performance and environmental information disclosure [37], Xiao et al found that the social environment of a country affected enterprise environmental performances [38], Pineiro-Chousa, Romero-Castro, and Vizcaíno-González argued that socially responsible investment indices could provide a new analysis approach for assessing the relationship between corporate financial and corporate environmental performances [39], and Farooq found that employee participation had a strong and positive impact on corporate environmental performance [40]. Other studies have analyzed the relationships between environmental performance and industrial structure, international trade, and technology, and others have suggested specific environmental supervision, market structures, and lean production developments for management decision-making in China's eco-industrial demonstration parks [41][42][43][44].…”
Section: Factors Affecting Environmental Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Most environmental performance research has been focused on determining the internal and external factors and identifying the related laws to verify the relationships between corporate environmental performance and financial performance [33][34][35][36]. For example, Yin and Ma found that the environmental standards adopted by enterprises could not be equated with their actual environmental performances [36], Dawkin and Fraas collected data from 500 S&P companies and proved that there was a U-type relationship between environmental performance and environmental information disclosure [37], Xiao et al found that the social environment of a country affected enterprise environmental performances [38], Pineiro-Chousa, Romero-Castro, and Vizcaíno-González argued that socially responsible investment indices could provide a new analysis approach for assessing the relationship between corporate financial and corporate environmental performances [39], and Farooq found that employee participation had a strong and positive impact on corporate environmental performance [40]. Other studies have analyzed the relationships between environmental performance and industrial structure, international trade, and technology, and others have suggested specific environmental supervision, market structures, and lean production developments for management decision-making in China's eco-industrial demonstration parks [41][42][43][44].…”
Section: Factors Affecting Environmental Performancementioning
confidence: 99%
“…The theory of scale economy and management economic market structure states that the larger the enterprise scale, the greater its influence in the market. To avoid monopoly, however, large-scale enterprises are subject to greater government regulation and are more affected by government environmental policies, regulations, and standards [39,40]. Second, the larger the enterprise, the more attention the daily business activities receive from stakeholders.…”
Section: Hypothesismentioning
confidence: 99%
“…Oberndorfer et al (2013) discuss that the underlying rationale of sustainability would suggest expected future profits without any effect on the short term. Similarly, the exclusion of a company in an index should negatively affect the levels of financial performance in the short term (Pineiro-Chousa et al, 2019). In this sense, Russo & Mariani (2013) highlight that exclusion has two negative meanings.…”
Section: Working Hypothesesmentioning
confidence: 99%
“…Specialist studies have shown a correlation between the independence of the audit committee, the level of supervision, and the level of fraud in the financial statements such as: the independence of audit committee members influences the reliability of financial statements [39,50]; committees composed of a certain percentage of external directors are more independent than other committees [33,45,51,52]; a positive influence of the audit committee is exerted on the quality of earnings [46] or the quality of the financial statements [53]; the effectiveness of the audit committee influences the timely presentation of financial statements [52][53][54][55][56].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Another correlation identified by the specialists is related to the degree of responsibility, the expertise of the members of the audit committee, and the financial performance. In fulfilling its supervisory, internal control, and financial reporting responsibilities, the audit committee should have the necessary expertise based on accounting and financial forecasting [55][56][57], accounting, control, and auditing [58] to ensure the superior quality of financial reporting [59]. Tenure, the regularity of the consultations, and social ties can also have an impact of great significance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%